1995
DOI: 10.2466/pms.1995.81.3f.1203
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Innovators, Sensation Seekers, and Clothing Individualists

Abstract: The purpose was to investigate the association of fashion consumer groups' scores on sensation seeking and clothing individuality. Fashion innovators are expected to be sensation seekers and to use clothing to express their individuality. 142 undergraduate students were administered Hirschman and Adcock's Measure of Innovativeness and Opinion Leadership, Zuckerman's Sensation Seeking Scale, and the Creekmore Clothing Interest Scale. Analysis showed that there was a significant mean difference between fashion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 8 publications
7
42
0
Order By: Relevance
“…The range of observed scores on the Need For Touch scale (À32 to þ 36) encompassed nearly the entire possible range (À36 to þ36). The mean score of 15.38 was consistent with earlier research: M ¼ 18.1 (Stanforth, 1995); M ¼ 15.29 (Studak & Workman, 2004); M ¼ 16.89 (Workman & Kidd, 2000). The range of scores on the Fashion Innovativeness and Opinion Leadership scale encompassed the entire possible range of 0-24.…”
Section: Resultssupporting
confidence: 86%
“…The range of observed scores on the Need For Touch scale (À32 to þ 36) encompassed nearly the entire possible range (À36 to þ36). The mean score of 15.38 was consistent with earlier research: M ¼ 18.1 (Stanforth, 1995); M ¼ 15.29 (Studak & Workman, 2004); M ¼ 16.89 (Workman & Kidd, 2000). The range of scores on the Fashion Innovativeness and Opinion Leadership scale encompassed the entire possible range of 0-24.…”
Section: Resultssupporting
confidence: 86%
“…In light of the findings of previous studies that linked personality traits to fashion consciousness (Stranforth 1995;Summers 1970), this study postulates that certain personality traits may be significantly associated with a high level of fashion consciousness. For instance, highly extroverted people value social interaction and thus may be more concerned with how others perceive the way they are dressed.…”
Section: Fashion Consciousnessmentioning
confidence: 68%
“…Stranforth (1995) found that fashion innovators are related to traits such as "sensation seeking," "adventure seeking," "susceptibility," and "clothing individuality." They were also found to be better educated, possess higher income, and actively engage in travel, sports, and entertainment activities (Crask and Reynolds 1978).…”
Section: Fashion Consciousnessmentioning
confidence: 99%
“…For example, earlier (vs. later) adopters had a greater need for variety (mental stimulation), were higher on sensation seeking and experience seeking, were less susceptible to boredom, and were more innovative [49][50][51][52]. Earlier (vs. later) adopters scored higher on change, risk, and unusual stimuli subscales of the arousal seeking tendency scale [49].…”
Section: Creative Attitudes and Time Of Adoptionmentioning
confidence: 99%